Monetary and fiscal regimes policy rules in a discrete time model - Norlin Khalid (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper determines how fiscal policy rule interacts with monetary policy rule affect the conditions of equilibrium determinacy when moving from continuous to discrete time. The monetary authority follows an interest rate-targeting rule while the fiscal authority follows a debt-targeting rule. It is shown that the local determinacy of an equilibrium path is determinate under the active monetary/passive fiscal regime, while the examination of other regimes is shown to be indeterminate. These findings are in stark contrast with the case of the continuous time model, suggesting that the timing assumptions play an important role in determining local equilibrium.